Cold Temperature Encoding by Cutaneous TRPA1 and TRPM8-Carrying Fibers in the Mouse - Winter, Zoltan; Gruschwitz, Philipp; Eger, Stephanie; Touska, Filip; Zimmermann, Katharina (Frontiers in Molecular Neuroscience, 2017)
Previous research identified TRPM8 and TRPA1 cold transducers with separate functions, one being functional in the non-noxious range and the second one being a nociceptive transducer. TRPM8-deficient mice present overt deficits in the detection of environmental cool, but not a lack of cold avoidance and TRPA1-deficient mice show clear deficits in some cold nocifensive assays. The extent of TRPA1's contribution to cold sensing in vivo is still unclear, because mice lacking both TRPM8 and TRPA1 (DKO) were described with unchanged cold avoidance from TRPM8-/- based on a two-temperature-choice assay and by c-fos measurement. The present study was designed to differentiate how much TRPM8 alone and combined TRPA1 and TRPM8 contribute to cold sensing. We analyzed behaviour in the thermal ring track assay adjusted between 30°C and 5°C and found a large reduction in cold avoidance of the double knockout mice as compared to the TRPM8-deficient mice. We also revisited skin-nerve recordings from saphenous-nerve skin preparations with regard to nociceptors and thermoreceptors. We compared the frequency and characteristics of the cold responses of TRPM8-expressing and TRPM8-negative C-fiber nociceptors in C57BL/6J mice with nociceptors of TRPM8-deficient and DKO mice and found that TRPM8 enables nociceptors to encode cold temperatures with higher firing rates and larger responses with sustained, static component. In TRPM8-/-, C-fiber cold nociceptors were markedly reduced and appeared further reduced in DKO. Nevertheless, the remaining cold responses in both knockout strains were similar in their characteristics and they were indifferent from the TRPM8-negative cold responses found in C57BL/6J mice. TRPM8 had a comparably essential role for encoding cold in thermoreceptors and lack of TRPM8 reduced response magnitude, peak and mean firing rates and the incidence of thermoreceptors. The encoding deficits were similar in the DKO strain. Our data illustrate that lack of TRPA1 in TRPM8-deficient mice results in a disproportionately large reduction in cold avoidance behaviour and also affects the incidence of cold encoding fiber types. Presumably TRPA1 compensates for lack of TRPM8 to a certain extent and both channels cooperate to cover the temperature range, making cold-temperature encoding by TRPA1 – although less powerful – synergistic to TRPM8.